Gender and trauma - (:unkn) unknown (Springer International Publishing, 2015)
A review of the literature on gender and trauma reveals that in many studies the term gender is employed as if it were synonymous with the term sex. Gender is not a biological reality, but a sociocultural construct that enables researchers to distinguish constitutional characteristics from socially acquired ones. Gender ought to be used as an analytical tool to understand social interactions, inequalities and human experiences including suffering. © Springer International Publishing Switzerland 2015.